2022
DOI: 10.3389/fonc.2022.932786
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Pyroptosis-Related Genes in Predicting Prognosis and Immunological Characteristics of Pancreatic Cancer From the Perspective of Genome and Transcriptome

Abstract: ObjectiveTo probe into the role of pyroptosis-related genes in pancreatic carcinoma.MethodsHerein, we conducted a comprehensive bioinformatics analysis to evaluate tumor-immune infiltration and tumor mutation burden, the correlations between PRGs, and microsatellite instability and found that 33 PRGS were up- or down-regulated in PC. Then we built the PPI network, which was downloaded from the STRING database. Using TCGA cohort median risk score, PC subjects from the Gene Expression Composite cohort (GEO) data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…As described by Li et al, this study revealed that NLRP1, NLRP2, IL18, and CASP4 overexpression may contribute to a lower overall survival rate in pancreatic cancer. In this study, TNF was also underexpressed in pancreatic cancer cells [77]. Another study employing almost different PRGs in developing the risk model revealed that the high-risk group decreased anti-tumor immunity by impairing CD8 T and NK cell infiltration in the TME of pancreatic cancer.…”
Section: Correlation Among Prgs Immune System Metabolism and Signalin...mentioning
confidence: 49%
See 1 more Smart Citation
“…As described by Li et al, this study revealed that NLRP1, NLRP2, IL18, and CASP4 overexpression may contribute to a lower overall survival rate in pancreatic cancer. In this study, TNF was also underexpressed in pancreatic cancer cells [77]. Another study employing almost different PRGs in developing the risk model revealed that the high-risk group decreased anti-tumor immunity by impairing CD8 T and NK cell infiltration in the TME of pancreatic cancer.…”
Section: Correlation Among Prgs Immune System Metabolism and Signalin...mentioning
confidence: 49%
“…Functional enrichment analysis of PRGs revealed that PRGs were mainly involved in pyroptosis, apoptosis, and other immune signaling pathways (TNF, TLR, and inflammatory response), indicating a conversation among the genome, signaling pathways, and the immune system to connect apoptotic cell death with pyroptosis [77].…”
Section: Correlation Among Prgs Immune System Metabolism and Signalin...mentioning
confidence: 99%
“…Furthermore, the downregulation of NLRP1 is correlated with unfavorable DFS in CHOL. Several studies have explored the potential of NLRP1 as a prognostic biomarker in various cancers, including lung adenocarcinoma [39,40,44], gastric cancer [45], prostate cancer [43], pancreatic cancer [46,47], head and neck squamous cell carcinoma [48], and laryngeal carcinoma [49]. Shen et al con rmed that decreased expression of NLRP1 was signi cantly associated with a poor prognosis of LUAD [41].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to these studies, our study also carried out methods such as survival analysis, ROC and external cohort validation of PMSRPS, but it still has its advantages. First, after knowing the importance of subtyping based on molecular characteristics of cancer for improving clinical treatment decision-making, we did not directly use PRGs to establish a prognostic signature as many previous studies had done (84)(85)(86)(87)(88), but instead identified three stable pyroptosis molecular subtypes based on PRGs expression levels. By analysis, we found that different PRGclusters had different survival outcomes and immune cell infiltration manifestations.…”
Section: Discussionmentioning
confidence: 99%